KONSUMSI, DIVERSIFIKASI DAN KETAHANAN PANGAN TINGKAT RUMAH TANGGA DI DAERAH ISTIMEWA YOGYAKARTA - , Ismiasih ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research are to determine: 1) the level of participation of household food consumption, and the factors influencing and the elasticity of food consumption, 2) diversification of household food consumption, and the factors influencing, 3) the level of household food security and the factors influencing, 4) the effect of poverty and diversification program on consumtion food on household food security. This research was taken at Yogyakarta as the research location. It employed the secondary data from Social and Economic National Surveyâs (Susenas) result of the Central Bureau of Statistics (BPS) in 2011. The samples are 925 households. The participation rate of food consumption were analyzed descriptively. Determining factor of food consumption at the household level is analyzed with a model Ordinary Least Square (OLS) estimated by the method of Seemingly Unrelated Regression (SUR) by inserting restriction on the nature of the demand function (Engel and Cournot Aggregation). Diversification of food consumption is measured by the entropy index. The deciding factor diversification of food consumption estimated by the model Ordinary Least Square (OLS). The level of household food security was measured with a modified Jonnsson and Toole. Factors determining the level of household food security in the model analyzed with ordinary least squares (OLS). The results showed that : 1 ) the level of participation of rural household food consumption 99 % in grain dominance in urban and 99 % in the dominance of food and beverages. Lowest participation level of food consumption in both urban and rural derived from tubers is 34 % . The deciding factor is influenced by food consumption food prices alone, prices of other food, income, number of household members, age of the wife, the wife of education, type of occupation of household head, household (non raskin- raskin , non poor-poor) and the location residence (urban and rural)